STUDY OF COMPOSITION AND STRUCTURE OF UNDERGROWTH VEGETATION IN AREAS INVADED BY INVASIVE ALIEN SPECIES BELLUCIA PENTAMERA NAUDIN IN CONSERVATION AREA OF PT. TKA SOUTH SOLOK - Solfiyeni; Indriani (Jurnal Metabio, 2022)
The invasion of alien plants such as Bellucia pentamera can reduce biodiversity in the conservation forest area. Analysis of undergrowth vegetation in the area invaded by invasive alien plants Bellucia pentamera Naudin in the Conservation Area of PT. TKA Solok Selatan in MarchAugust 2020. This study aims to determine the composition and structure of undersgrowth vegetation in areas invaded by invasive alien plants Bellucia pentamera and to see the effect of distance from the road on the distribution of Bellucia pentamera tillers. The method used in this research is the quadratic method with belt transects of 2 x100 meters from the edge of the forest to the forest. The composition of understorey in the Conservation Area of PT. TKA were found as many as 48 species from 32 families. The distance from the highway affects the light intensity and also affects the distribution of the number of B. pentamera seedling individuals. The highest important value index of undergrowth was Shorea leprosula, Bellucia pentamera, and Clidemia hirta with a value of 40.51%; 29.20%; 19.43% while the diversity index (H ') of undergrowth with a value of 3.0 means that the diversity index is classified as medium.